Identification of Pollutant Distribution in Kaliotik River Water Through Oxygen Levels, EPT, and Biotic Index - Sulistiono, Eko; Syakbanah, Nur Lathifah; Agustin, Vindi Erina (Universitas Pembangunan Nasional Veteran Jawa Timur, 2025)
River water pollution has now become a serious problem for society with population growth. The development of various industries and pesticides usage. One of the rivers in Lamongan, namely Kaliotik is heavily polluted. One of the rivers in Lamongan, namely Kaliotik is heavily polluted. Therefore, the research aim is to analyze the distribution of Kaliotik River water quality pollution zones. The research type is a quantitative descriptive analysis, with the research design used the true experimental time series design. Identification of river pollution zones along the Kaliotik river is based on the self-purification zone. contamination zone is identified based on the content of BOD, COD, DO as well as microscopic and biometric tests of the diversity of water organisms. River water quality assessment using Biotilics is carried out by calculating the diversity of family types, the diversity of EPT types, percentage of EPT abundance, and the Biotilic Index. The results of the research showed that Station I obtained a biotylic index of 2.45; Station II obtained a biotylic index of 2.66; station III obtained a biotylic index of 2.82; Station IV obtained a biotylic index of 2.82 and Station V obtained a biotylic index of 2.97. From these results it can be concluded that the Kaliotik river is heavily polluted and in a polluted zone.